2010
DOI: 10.1080/10584581003591049
|View full text |Cite
|
Sign up to set email alerts
|

Pyroelectric Properties of Epitaxial (001) Barium Strontium Titanate as a Function of Space Charge Density

Abstract: A non-linear thermodynamic model was developed to investigate the effect of charge compensation on polarization and pyroelectric properties of graded monodomain ferroelectric multilayers. To represent charge compensation at the interfaces, a dimensionless parameter, "coupling strength," was introduced. Heterostructures in which interfaces are perfectly insulating so that coupling strength is maximized behave as if they are a single ferroelectric material. Upon introduction of localized space charges to the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…[12] (b) Evolution of ferroelectricity should follow the variation in coupling strength between different layers. [17,18] (c) The spontaneous polarization in the PE layer derived by thermodynamic theory should be consistent with the electricfield-induced polarization, which can be obtained from the relation between the electric field and dielectric constant. [19] We basically consider an FE-PE bilayer between electrodes on a substrate which is much thicker than the bilayer under short-circuit electrical boundary conditions.…”
mentioning
confidence: 74%
See 4 more Smart Citations
“…[12] (b) Evolution of ferroelectricity should follow the variation in coupling strength between different layers. [17,18] (c) The spontaneous polarization in the PE layer derived by thermodynamic theory should be consistent with the electricfield-induced polarization, which can be obtained from the relation between the electric field and dielectric constant. [19] We basically consider an FE-PE bilayer between electrodes on a substrate which is much thicker than the bilayer under short-circuit electrical boundary conditions.…”
mentioning
confidence: 74%
“…From a physical point of view, it is necessary to consider their results seriously. In our previous study, we found that treating coupling strength as an adjustable parameter in some phenomenological models [17,18] to describe the electrostatic coupling with interfacial space charge is inappropriate. [19] In this study, we examine the validity of their models [9βˆ’15] regardless of the forgoing important physical problems.…”
mentioning
confidence: 99%
See 3 more Smart Citations